A Highlight of the Mechanisms of Immune Checkpoint Blocker Resistance - Huang, Qian; Lei, Yanna; Li, Xiaoying; Guo, Fukun; Liu, Ming (Frontiers in Cell and Developmental Biology, 2020)
In recent years, as our understanding of tumor immunology is continuously improved, immunotherapy has come to the center stage of cancer therapy and is deemed as the most promising approach for cancer control. Although immunotherapy, particularly immune checkpoint blockade(ICB), has achieved a milestone in several types of tumors, the majority of cancer patients do not benefit from immunotherapy. The dismal outcome of cancer immunotherapy is mainly due to primary or acquired resistance arising from tumor immune evasion. Exploring the mechanisms of tumor immune evasion in the course of immunotherapy may identify biological targets to conquer tumor resistance to immunotherapy. In this review, we highlight tumor cell-intrinsic and -extrinsic factors that may underlie tumor resistance to immune checkpoint blockers. Targeting these factors in combination with immune checkpoint blockers points to the future direction of cancer immunotherapy.